Solar Radiation Exposure Has Diurnal Effects on Thermoregulatory Responses During High-Intensity Exercise in the Heat Outdoors. Issue 10 (October 2019) - Otani, Hidenori; Goto, Takayuki; Goto, Heita; Hosokawa, Yuri; Shirato, Minayuki
Abstract : Abstract: Otani, H, Goto, T, Goto, H, Hosokawa, Y, and Shirato, M. Solar radiation exposure has diurnal effects on thermoregulatory responses during high-intensity exercise in the heat outdoors. J Strength Cond Res 33(10): 2608–2615, 2019—This study investigated the diurnal effects of variations in solar radiation associated with changing solar elevation angle on thermoregulatory responses during high-intensity exercise in the heat outdoors. Ten male high school soccer players completed two 2-hour soccer training sessions under a clear sky in the heat of summer. These sessions were commenced at 0900 hours (AM) and 1600 hours (PM) on separate days. Solar radiation and elevation angle were higher in AM (820–1, 070 W·m −2 and 45–69°) than PM (620–110 W·m −2 and 34–10°: both p < 0.001). Neither ambient temperature (AM 29–32° C; PM 31–31° C) nor wet-bulb globe temperature was different between trials. Although mean skin temperature was not different between trials, infrared tympanic temperature was higher at the end of exercise in AM than PM ( p < 0.001). Heart rate ( p < 0.01) and body heat gain from the sun ( p < 0.001) were greater during exercise in AM than PM. Dry heat loss was smaller, but evaporative heat loss was greater in AM than PM (both p < 0.001). Thermal sensation and rating of perceived exertion were similar between trials, but GPS measurements showed a less total distance and distance covered by walking, jogging, and running in AM than PM ( p < 0.01). This study demonstrates a greater thermoregulatory strain in AM than PM during 2-hour high-intensity soccer training in the heat under a clear sky. This observation is accompanied by a progressive increase in environmental heat stress with rising solar radiation and elevation angle in AM and a greater body heat gain from the sun in AM compared with PM.